Ultra‐sensitive speciation analysis of mercury by CE‐ICP‐MS together with field‐amplified sample stacking injection and dispersive solid‐phase extraction. Issue 7 (29th December 2015) - Chen, YiQuan; Cheng, Xian; Mo, Fan; Huang, LiMei; Wu, Zujian; Wu, Yongning; Xu, LiangJun; Fu, FengFu
Abstract : A simple dispersive solid‐phase extraction (DSPE) used to extract and preconcentrate ultra‐trace MeHg, EtHg and Hg 2+ from water sample, and a sensitive method for the simultaneous analysis of MeHg, EtHg and Hg 2+ by using capillary electrophoresis‐inductively coupled plasma mass spectrometry (CE‐ICP‐MS) with field‐amplified sample stacking injection (FASI) were first reported in this study. The DSPE used thiol cotton particles as adsorbent, and is simple and effective. It can be used to extract and preconcentrate ultra‐trace mercury compounds in water samples within 30 min with a satisfied recovery and no mercury species alteration during the process. The FASI enhanced the sensitivity of CE‐ICP‐MS with 25‐fold, 29‐fold and 27‐fold for MeHg, EtHg and Hg 2+, respectively. Using FASI‐CE‐ICP‐MS together with DSPE, we have successfully determined ultra‐trace MeHg, EtHg and Hg 2+ in tap water with a limits of quantification (LOQs) of 0.26–0.45 pg/mL, an RSD ( n = 3) < 6% and a recovery of 92–108%. Ultra‐high sensitivity, as well as much less sample and reagent consumption and low operating cost, make our method a valuable technique to the speciation analysis of ultra‐trace mercury.